Cognitive Development Media of Children: Development of Educational Toys Mandalika Cockroach Racing Circuit - Putri Riana; Heldanita Heldanita; Nurhasanah Bakhtiar; Nurkamelia Mukhtar AH; Wahyuni Murniati; Gamal Abdul Nasir Zakaria; Yossy Irawan (Departemen Penelitian dan Pengembangan Perkumpulan Program Studi PAUD Indonesia, 2024)
This study aims to develop the Mandalika Cockroach Racing Circuit, an educational play tool designed to stimulate the cognitive development of early childhood learners, and to evaluate its feasibility. The research employs a Research and Development approach using the ADDIE model. The subjects involved were teachers and children aged 5–6 years at TK Aisyiyah Menaming. Data were collected through questionnaires, observation, and documentation, and analyzed using expert validation input and Likert scale responses. The results show that media experts rated the product at 81.25%, material experts at 93.3%, and school principals and teachers at 92%, indicating a